Exploring the syntheses, structures, topologies, luminescence sensing and magnetism of Zn(ii) and Mn(ii) coordination polymers based on a semirigid tricarboxylate ligand. Issue 36 (30th August 2018) - Li, Shaodong; Lu, Liping; Zhu, Miaoli; Feng, Sisi; Su, Feng; Zhao, Xuefeng
Abstract : Two Zn(ii )-CPs and two Mn(ii )-CPs were constructed from metal salts, H3 cpota and N-heterocyclic group ligands. Their structures, magnetic properties and luminescence sensing properties have been studied in detail. Abstract : Solvothermal reactions of Zn(ii ) or Mn(ii ) salts and 2-(4-carboxyphenoxy)terephthalic acid (H3 cpota) in the presence of N-heterocyclic group ligands (1, 10-phenanthroline (phen) or 1, 4-di(1 H -imidazol-1-yl)benzene (bib) or 4, 4′-bipyridine (4, 4′-bpy)) produced four multi-dimensional coordination polymers, namely, [Mn(μ3 -Hcpota)(phen)] n · n H2 O1 (1D), [Mn2 (μ4 -Hcpota)(μ3 -Hcpota)(μ2 -bib)2 (H2 O)] n 2 (3D), [Zn(μ3 -Hcpota)(phen)] n · n H2 O3 (2D), and [Zn2 (μ4 -cpota)(μ2 -4, 4′-bpy)(μ3 -OH)] n · n H2 O4 (3D). Complex1 features a one-dimensional double ladder formed by syn – anti carboxylate-bridged dimeric Mn(ii ) units with 8- and 26-membered rings in an alternating pattern sharing three atoms and gives a (4 2 ·6) topology. Complex2 is formed by linear inorganic chains sharing Mn(ii ) 8-membered rings in double syn – syn carboxylate bridges and H-bond R11(8) alternate modes, which are further connected to each other by two symmetry independent Hcpota 2− ligands as well as coordinated bib bridges giving rise to a three-dimensional net with a novel (4·6 2 )(4·6 8 ·8)(4 3 ·6 11 ·8)(4 3 ·6 3 ) topology. Complex3 exhibits a two-dimensional layered structure containing 36-membered rings based on 8-membered dinuclear Zn(ii ) units with (3 2 ·4 4 )(3 4 ·4 6 ·6 4 ·7)fes -net topology. The phen and benzoic acid groups are like two kinds of blades in the two sides of the two-dimensional structure of3 . Complex4 is an interesting three-dimensional (3, 8)-connected network including tetranuclear tricyclic [Zn4 (OH)2 (COO)6 ] clusters with a new (4·5·6)2 (4 2 ·5 6 ·6 16 ·7 2 ·8 2 ) topology. The semirigid tricarboxylate ligand (H3 cpota) shows three geometric modes in the self-assembly of four coordination polymers: a) 'L' shape in1, b) 'I' shape in2 and3, and c) 'T' shape in4 . Magnetization analyses disclose the antiferromagnetic behaviors of1 and2 . Complexes3 and4 feature good solvent stability and can withstand ten common solvents. Luminescence investigations reveal that complex3 has a highly sensitive, selective, low detection limit and well-recyclable properties in the detection of hexavalent chromium anions in aqueous solution. Quenching mechanisms are also studied in detail.